2018
DOI: 10.1007/s10549-018-4670-9
|View full text |Cite
|
Sign up to set email alerts
|

Living with chronic pain: perceptions of breast cancer survivors

Abstract: One in three postmenopausal, HR+ BCS considered themselves to be living with chronic pain. Effective interventions to reduce chronic pain are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…Musculoskeletal pain was the most common indication associated with concomitant oral analgesics in our analysis. This is consistent with previous reports by Fenlon et al [23] and Bao et al [26], which also found high rates of musculoskeletal pain in patients with breast cancer following surgery but before adjuvant therapy and in breast cancer survivors with current or prior use of aromatase inhibitors.…”
Section: Discussionsupporting
confidence: 93%
“…Musculoskeletal pain was the most common indication associated with concomitant oral analgesics in our analysis. This is consistent with previous reports by Fenlon et al [23] and Bao et al [26], which also found high rates of musculoskeletal pain in patients with breast cancer following surgery but before adjuvant therapy and in breast cancer survivors with current or prior use of aromatase inhibitors.…”
Section: Discussionsupporting
confidence: 93%
“…Individual characteristics (eg, age, income) and clinical factors (eg, cancer stage, time since diagnosis) contribute to survivors' QOL . A common complaint, chronic pain, is reported by up to 78% of survivors, and thought to be related to poor QOL outcomes . This highlights a need to expand access to evidence‐based QOL management tools that are capable of supporting a wide range of individual needs.…”
Section: Introductionmentioning
confidence: 99%
“…Intense pain during the first hours or days following surgery has been shown to be strongly associated with the emergence of persistent pain, defined as the presence of pain three or more months after surgery (Feizerfan & Sheh, 2015; Schneiderhan, Clauw, & Schwenk, 2017). In addition, for oncological patients undergoing a psychologically vulnerable period shortly after the diagnosis of breast cancer, avoidance of acute pain is central (Bao et al., 2018; Peuckmann et al., 2009).…”
Section: Introductionmentioning
confidence: 99%